Management of Post Infarction Ventricular Septal Defect - Paul, Shimu; Islam, Md Sirajul; Roy, Siba Pada; Ahmed, Niaz; Mina, MH; Md Jalaluddin, - (Ibrahim Cardiac Medical Journal, 2015)
Ventricular septal rupture remains an infrequent but a serious, devastating and life threating complication of acute myocardial infarction. We report a case of 74 years old man with post infarction anterior ventricular septal rupture who was successfully managed. Ventricular septal rupture was closed by artificial (gortex) patch; concomitant coronary artery bypass grafting was done. Postoperative complications included reopening for excessive bleeding, low cardiac output with high inotropic support. A rapid diagnosis, aggressive medical management and prompt surgical intervention are required to optimize survival and recovery in patients who present with septal rupture complicating myocardial infarction. Ibrahim Cardiac Med J 2013; 3(1&2): 49-52